Alcian blue staining to track the intracellular fate of hyaluronic-acid-based nanoparticles at transmission electron microscopy - Carton, Flavia (Eur J Histochem, 2019)
The main step in the assessment of nanomaterial safety and suitability for biomedical use is the location and the dynamic tracking of nanoparticles (NPs) inside cells or tissues. To precisely investigate the uptake mechanisms and intracellular fate of NPs, transmission electron microscopy is the technique of choice; however, the detection of NPs may sometimes be problematic. In fact, while NPs containing strongly electron dense (e.g. metal) components do not require specific detection methods at the ultrastructural level, organic NPs are hardly detectable in the intracellular environment due to their intrinsic moderate electron density. In this study, the critical-electrolyte-concentration Alcian Blue method set up by Schofield et al. in 1975 was applied to track hyaluronic-acidbased NPs in muscle cells in vitro. This long-established histochemical method proved to be a powerful tool allowing to identify not only whole NPs while entering cells and moving into the cytoplasm, but also their remnants following lysosomal degradation and extrusion.